Phosphorylated cardanol prepolymer‐grafted carboxylated styrene–butadiene rubber for better processing with enhancing silica filler dispersion. Issue 20 (15th January 2019) - Prabhavale, Onkar; Mahata, Denial; Nando, Golok B.
ABSTRACT: Cardanol is a byproduct of cashew industry of semiforest origin. It is cheap and available in humongous amount and acts as a multifunctional additive in rubber compounds. It can be oligomerized with orthophosphoric acid to make phosphorylated cardanol prepolymer (PCP). Hence, cardanol has been chemically grafted on to the backbone chain of carboxylated styrene–butadiene rubber (XSBR) by employing melt grafting technique in presence of peroxide initiator to include multifunctional properties. The PCP‐grafted XSBR (PCP‐ g ‐XSBR) was characterized by using Fourier transform infrared spectroscopy and 1 H‐NMR techniques and optimize the grafting conditions such as percent of grafting and grafting efficiency by using Taguchi methodology. PCP‐ g ‐XSBR was compounded with silica filler for a comparative study in terms of processing behavior with XSBR. The cure characteristics such as the cure rate and the optimum cure time of the unfilled PCP‐ g ‐XSBR compounds were determined by oscillating disc rheometer. The thermal analysis of PCP‐ g ‐XSBR vulcanizate exhibits slightly better thermal stability as well as plasticization effect. Morphological behaviors also display the less cracked and filled fracture surfaces with better filler dispersion in PCP‐ g ‐XSBR vulcanizate. The mechanical properties of the compounded PCP‐ g ‐XSBR vulcanizates also improve compare to XSBR vulcanizates. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47528. Abstract : The phosphorylated cardanol prepolymer‐grafted carboxylated styrene–butadiene rubber (XSBR) exhibits the better processing characteristics with silica filler dispersion compare to neat XSBR.